Effect of adding macro and micro minerals in pig feces fed diets with different levels of probiotic - Huaynate, Rizal Alcides Robles [UNESP]; Thomaz, Maria Cristina [UNESP]; Kronka, Rodolfo Nascimento [UNESP]; Fraga, Alessandro Luís [UNESP]; Scandolera, Antônio João [UNESP]; Budiño, Fábio Enrique Lemos [UNESP] (Brazilian Archives of Biology and Technology, 2006)
O objetivo deste trabalho foi avaliar dietas contendo diferentes doses (0, 100, 200 e 300 ppm) de probiótico sobre a produção diária de fezes (PDF) e teor de macro e microminerais nas fezes de suínos, nas fases de creche e de crescimento e no período total. A PDF, como porcentagem do peso vivo, somente apresentou diferença estatística (P<0,05) na fase inicial 1. Os teores de macro e microminerais excretados nas fezes não apresentaram diferença (P>0,05) entre tratamentos, a exceção de cálcio e sódio na fase inicial 1 e cálcio, zinco e níquel no período total. A adição de um poliprobiótico às dietas, não afetou a produção de fezes dos suínos nas fases de creche e de crescimento. Entretanto, a presença de microrganismos, adicionados (níveis de 200 e 300 ppm) às dietas reduziu a excreção fecal de cálcio, zinco e níquel.

This study aimed to verify the effect of diets with different doses (0, 100, 200 and 300 ppm) of probiotic on daily fecal production (DFP) and level of macro and micro minerals in feces of nursing (1st and 2nd initial phases) and growing pigs and during total period. The DFP, as percentage of body weight, was different (P<0.05) among treatments only at 1st initial phase. Fecal levels of macro and micro minerals were similar (P>0.05) among treatments, with exception of calcium and sodium excretion at 1st initial phase and calcium, zinc and nickel during total period. The addition of a poliprobiotic to diets do not affect fecal production of nursing and growing pigs. However, the presence of microorganisms, added (levels of 200 and 300 ppm) in diets for nursing and growing pigs reduced fecal excretion of calcium, zinc and nickel.
Keywords: Calcium; digestion; Lactobacillus; Piglet; zinc